2017
DOI: 10.1016/j.spmi.2016.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of bandgap in bilayer armchair graphene ribbons by tuning vertical and transverse electric fields

Abstract: We investigate the effects of external electric fields on the electronic properties of bilayer armchair graphene nano-ribbons. Using atomistic simulations with Tight Binding calculations and the Non-equilibrium Green's function formalism, we demonstrate that (i) in semi-metallic structures, vertical fields impact more effectively than transverse fields in terms of opening larger bandgap, showing a contrary phenomenon compared to that demonstrated in previous studies in bilayer zigzag graphene nano-ribbons; (ii… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…In contrast, without external fields applied, the structure M = 14 (group 3p + 2) exhibits as semimetallic and in agreement with the conclusions in previous studies. [19] In the presence of a vertical electric field, the bandgap of former groups becomes narrower whereas it increases in the later one.…”
Section: The Impact Of the Vertical Electric Field On The Band Structmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, without external fields applied, the structure M = 14 (group 3p + 2) exhibits as semimetallic and in agreement with the conclusions in previous studies. [19] In the presence of a vertical electric field, the bandgap of former groups becomes narrower whereas it increases in the later one.…”
Section: The Impact Of the Vertical Electric Field On The Band Structmentioning
confidence: 99%
“…In Fig. 3 (a) As it has been demonstrated that the bandgap in BL-AGNRs and AGNRs strongly depends on the width of the structures, [19,23] it is thus relevant to investigate the interplay of the Seebeck coefficient and the number of dimer linesM. The maximum Seebeck coefficient of BL-AGNRs was deduced as a function of M for three characteristic groups of the width 3p, 3p + 1 and 3p + 2 and shown in Fig.…”
Section: The Intrinsic Thermoelectric Properties Of Bl-agnrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that in the BL-AGNR structure, the perpendicular electric field has a significant impact on tuning the bandgap of the material. On the other hand, the parallel electric field has a greater influence on the energy dispersion of zigzag bilayer graphene (Vũ & Trần, 2016;Vũ et al, 2017). Similar analytical calculations for each dimer line corresponding to each termination state have demonstrated that the maximum magnitudes of the gap are dissimilar for different critical potential strengths (Vũ & Trần, 2016;Vũ et al, 2017;Vũ et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…In addition to the infinite, two-dimensional bilayers, bilayer graphene nanostructures constitute a class of highly promising systems due to additional possibility of shaping their edge geometry to engineer the desired properties. This concerns, for example, one-dimensional nanoribbons [21][22][23][24][25][26][27][28]. It is also notable that highly non-trivial magnetic properties of bilayer zero-dimensional nanoflakes, in particular influenced by electric field, attracted considerable attention [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%